EROSION AND SEDIMENTATION ANALYSIS IN CEMPAKA AND GUNUNG KUPANG RESERVOIRS USING THE USLE METHOD IN CEMPAKA DISTRICT, BANJARBARU CITY - Fernanda, Joan Anthoni; Novitasari, Novitasari; Sofia, Elma (CERUCUK, 2025)
Floods are one of Indonesia's most frequent natural disasters, especially in densely populated cities. Major floods in February 2023 hit Cempaka and Gunung Kupang Districts. To overcome this problem, the government built the Cempaka Embung and the Gunung Kupang Embung to control flooding and increase water infiltration into the ground. Land use changes upstream of the reservoir greatly affect the reservoir, especially land erosion and sedimentation that enter the reservoir body, which will reduce the performance of the reservoir in reducing flooding. Therefore, erosion and sedimentation analysis is needed to support better management in flood control in Cempaka District. The data used in this study are land use data, soil type data, topographic data, conservation data, and location photos are secondary data. In this study, the rate of erosion and sedimentation was calculated using the USLE method. Based on the results of the analysis, it was found that the erosion rate of the USLE method in the Cempaka Reservoir was 131.934 tons/ha/year, and the sediment rate was 38.0765 tons/ha/year. In the Gunung Kupang Reservoir, the USLE method erosion rate was 18,790 tons/ha/year, and the sediment rate was 6,057 tons/ha/year.Keywords: Watershed Erosion, Reservoir Sediment, USLE, Reservoir